1) Nombre de départ : 5
5 X (- 7) = - 35
- 35 + 4 = - 31
Résultat : - 31
Nombre de départ : - 3
- 3 X (- 7) = 21
21 + 4 = 25
Résultat : 25
Nombre de départ : 0
0 X (- 7) = 0
0 + 4 = 4
Résultat : 4
Nombre de départ : 2
2 X (- 7) = - 14
- 14 + 4 = - 10
Résultat : - 10
Nombre de départ : - 8
- 8 X (- 7) = 56
56 + 4 = 60
Résultat : 60
2) Nombre de départ : - 6
- 6 X (- 7) = 42
42 + 4 = 46
Résultat : 46
Nombre de départ : 93/14
93/14 X (- 7) = - 46.5
- 46.5 + 4
Résultat : - 42.5
Nombre de départ : - 1
- 1 X (- 7) = 7
7 + 4 = 11
Résultat : 11